Gerakan Dakwah Siber di tengah Benturan Ideologi Komunitas Keagamaan - Minan Jauhari (Institut Agama Islam Negeri (IAIN) Sultan Amai Gorontalo, 2021)
This article analyzes the da'wah movement that is expressed in cyber media, as well as the challenges of implementing da'wah that must be carried out amid the clash of ideologies of religious communities. This study uses a qualitative method with an ethnomethodological approach, focusing on the analysis of digital conversations that are centered on the analysis of traces of interactions and conversations in response to da'wah narratives that have been uploaded openly through cyber community media. By using the concept of cyberspace and the concept of da'wah in understanding this cyber religious reality, this study can show that da'wah movements and activities that are displayed through cyber community media are a religious phenomenon along with the development of information and communication technology. This study also looks at the importance of humanist cyber da'wah by considering the da'wah process displayed in this cyber media in addition to calling for goodness and preventing evil, it also tends to describe the occurrence of ideological disputes and clashes between religious communities, marked by the many pro and con responses that appear in each da'wah message that uploaded through cyber religious community media.